Comparative in Vitro Antifungal Activity of Azadirachta Indica A. Juss. And Anacardium Occidentale L. Leaf Extracts Against Fungal Pathogens of Amaranthus Hybridus - Ewekeye, Tolulope S.; Adeyemi, Damilola R.; Oloyede, Olanrewaju J.; Akinyegun, Moyosoreoluwa A.; Fadiora, Adewumi; Oke, Oyedamola A. (FUDMA Journal of Sciences, 2026)
Fungal pathogens significantly affect the cultivation of Amaranthus hybridus, leading to reduced yield and quality. Environmental and health concerns associated with synthetic fungicides have increased interest in plant-based biofungicides as safer alternatives. This study evaluated the antifungal activity of aqueous leaf extracts of Azadirachta indica and Anacardium occidentale against Fusarium oxysporum, Alternaria tenuissima, and Aspergillus flavus. To obtain the extracts, 100 g of dried leaf powder was macerated in 1000 mL of distilled water. Antifungal activity was assessed using the poisoned food technique at 5%, 10%, and 15%. All treatments were replicated three times. The triplicates were analyzed by one-way analysis of variance (ANOVA), followed by Tukey’s post hoc test at p ≤ 0.05. Azadirachta indica demonstrated a clear but moderate concentration-dependent antifungal activity with all tested fungi. The highest inhibition was shown against Fusarium oxysporum (28.6 ± 2.5% at 15% concentration). Anacardium occidentale showed mild antifungal activity, with Alternaria tenuissima showing no observable inhibition at the tested concentrations. These findings indicate that A. indica demonstrates moderate but considerable antifungal potential for managing fungal diseases of Amaranthus hybridus. Further in vivo studies are recommended to validate field efficacy.
Keywords: Azadirachta indica; Anacardium occidentale; Antifungal activity; Biofungicides; Amaranthus hybridus; Poisoned food technique